Dynamic Visualization of the KU Distribution System - Neupane, Rupesh; Dhungana, Madhuraman; Luitel, Pratik; Gurung, Samundra (Journal of Science and Engineering, 2025)
The integration of Distributed Energy Resources (DERs) and Electric Vehicles (EVs) into traditional power distribution systems, often accompanied by uncoordinated extra load addition in distribution lines without knowing their hosting capacity, can lead to poor voltage quality, increased line losses, reduced hosting capability, and higher fault probabilities in the grid. These challenges underline the urgent need for real-time monitoring and visualization of the grid to support informed decision making by grid operators. This paper presents a near real-time visualization method developed for the Kathmandu University distribution network, where different electrical parameters are collected from seven smart meters installed at various buildings and the distribution transformer. These real-time data are transferred to Matpower, which contains the model of the studied distribution system. Using Newton-Raphson power flow analysis, the output monitoring parameters such as bus voltages, line losses, and line loadings are calculated and visualized through an interactive Node-RED dashboard. This dashboard offers intuitive schematic views, various graphical visualizations, and the ability to review grid parameters from past data, providing valuable insights into recent operational trends. The proposed system demonstrates an effective and scalable approach for enhancing situational awareness and reliability in modern distribution networks using open source technologies.